2023
DOI: 10.1186/s12864-023-09466-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulatory mechanism of key LncRNAs in subclinical mastitic cows with folic acid supplementation

Xueqin Liu,
Siyuan Mi,
Wenlong Li
et al.

Abstract: Background Folic acid is a water-soluble B vitamin (B9), which is closely related to the body’s immune and other metabolic pathways. The folic acid synthesized by rumen microbes has been unable to meet the needs of high-yielding dairy cows. The incidence rate of subclinical mastitis in dairy herds worldwide ranged between 25%~65% with no obvious symptoms, but it significantly causes a decrease in lactation and milk quality. Therefore, this study aims at exploring the effects of folic acid suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Recently a published research demonstrated that folic acid treatment significantly regulated LnRNA MSTRG.11108.1 in mastitic cows. The LncRNA MSTRG.11108.1 further regulated the genes (CXCL3, ICAM1, CXCL1, LHFPL2, LTF, ITGA9, and KIR3DL2) that were associated with immunity and inflammation ( 172 ). In addition, they also documented several immunity and immunity linked biological signaling pathways (B cell receptor signaling pathways, TNF signaling pathway, IL-17 signaling pathway and NF-κB signaling pathway) which is in consistent with findings reported previously ( 165 , 173 ).…”
Section: The Role Of Vitamins Supplementation In Mastitis Alleviationmentioning
confidence: 99%
“…Recently a published research demonstrated that folic acid treatment significantly regulated LnRNA MSTRG.11108.1 in mastitic cows. The LncRNA MSTRG.11108.1 further regulated the genes (CXCL3, ICAM1, CXCL1, LHFPL2, LTF, ITGA9, and KIR3DL2) that were associated with immunity and inflammation ( 172 ). In addition, they also documented several immunity and immunity linked biological signaling pathways (B cell receptor signaling pathways, TNF signaling pathway, IL-17 signaling pathway and NF-κB signaling pathway) which is in consistent with findings reported previously ( 165 , 173 ).…”
Section: The Role Of Vitamins Supplementation In Mastitis Alleviationmentioning
confidence: 99%